A GENRE ANALYSIS OF LANGUAGE USE BETWEEN TRADERS AND BUYERS IN ENGLISH VILLAGE PARE KEDIRI - Jenycha Fresy Ryandani (Graduate Program, University of Islam Malang, 2021)
Language is a means of communication in social interactions between one individual and another. With language, a language speaker can easily convey a message to the speech partner. The purposes of the research are; (1) Describing the variations of language used by the traders and buyers in buying and selling at English Village Pare Kediri (2) Describing the factors that influence the use of language to traders and buyers in buying and selling at English Village Pare Kediri.The method that was used in this research is a qualitative descriptive method. It is aims to describe the language used by traders and buyers in buying and selling transactions at English Village Pare and the factors that influence it. The subject was 10 participants of seller and buyer who sold and bought at English Village Pare Area. The instrument of collecting data in this research was using the observation.The steps that the researcher has applied are SPEAKING; S is for Setting and scene, P is for participant, E is for End, A is for a sequence, K is for Key, I is for Instrumentalities, N is form Norm, G is for Genre. Next, the findings of this research showed that factors that influence the use of language at English Village Pare, are; age, gender, level education and environment.The result of the study shows that the use of trader language in English Village Pare has diversity in communication. Traders who come from various ethnicities can become a multilingual society when they enter the English village, due to environmental factors. Factors such as age, gender, education and environment affect the use of the merchant's language during buying and selling transaction situation that creates language diversity.